A generalised damage model for masonry under compression. (July 2016) - Zahra, Tatheer; Dhanasekar, Manicka
A generalised model based on damage mechanics for predicting the response of masonry subjected to compression is presented. The model accounts for the behaviour of the constituents of the masonry, viz., the units, the mortar and the unit–mortar interfaces; in this paper, the unit–mortar interfaces and the mortar layers have been treated as a homogenised continuum. The principles of damage mechanics coupled with limiting damage surfaces have been used to simulate the behaviour of the masonry constituents. The novelty is the use of a non-linear, progressively stiffening stress–strain curve to simulate the viscoelastic behaviour of the homogenised mortar–interface (for conventional masonry) or dry surface–interface (for dry-stack masonry) layers until a threshold strain is reached. Beyond the threshold strain, their behaviour is assumed to have changed to progressive softening common for concrete like materials. The damage model for compression and tension due to progressive stiffening and softening criteria respectively have been formulated for the masonry constituents. The parameters which characterise the tensile and compressive behaviours, the volumetric change and the damage behaviour of the masonry constituents have been calibrated using some available experimental data in the literature. The model is shown to predict the average compressive strength and stress–strain behaviour of the masonry prisms appropriately. The model is capable of capturing the behaviour including appropriate stiffness degradation and post peak softening that are comparable to the experimental predictions reported in the literature for various types of masonry.